2018
DOI: 10.4136/ambi-agua.2120
|View full text |Cite
|
Sign up to set email alerts
|

Surface albedo in different land-use and cover types in Amazon forest region

Abstract: Albedo is the portion of energy from the Sun that is reflected by the earth's surface, thus being an important variable that controls climate and energy processes on Earth. Surface albedo is directly related to the characteristics of the Earth's surface materials, making it a useful parameter to evaluate the effects of original soil cover replacement due to human occupation. This study evaluated the changes in the surface albedo values due to the conversion of vegetation to other land uses and to analyze the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
1
7
0
5
Order By: Relevance
“…[75] observed that class names used in land cover classification systems are often descriptive without providing detail on the criteria used to define these classes. Water bodies and croplands fall within the literature ranges, while forest/plantation lies within 0.01 of published values for this land cover class, although lower than reported by [36].…”
Section: Land Cover Trajectoriessupporting
confidence: 81%
See 2 more Smart Citations
“…[75] observed that class names used in land cover classification systems are often descriptive without providing detail on the criteria used to define these classes. Water bodies and croplands fall within the literature ranges, while forest/plantation lies within 0.01 of published values for this land cover class, although lower than reported by [36].…”
Section: Land Cover Trajectoriessupporting
confidence: 81%
“…Additionally, the link between modelled landscape change, surface albedo and changes in catchment water and carbon fluxes have not been investigated. Recently, surface albedo was extracted from satellite data per land cover class for calibration of land surface models (LSM) in climate modelling [34,35], while other authors have investigated the potential of albedo in land cover [36] and land cover change analyses [17]. The aim of this paper is to quantify trends and relationships between land cover change, surface albedo, NPP and ET to characterise catchment water and carbon fluxes and postulate consequences on ecosystem services provided by grasslands.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the impact of forest structure gradients and change on albedo typically contrast forest with highly altered vegetation types canopies. For example, higher albedo is typically found in pasture, crops, and cleared lands, relative to forest, at least after initial post‐fire increases in absorptive charred materials subside (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019, Faria et al 2018). The albedo of regenerating secondary forest appears to converge toward mature forest values (low values, i.e., ~0.1); however, seasonal differences in albedo and net radiation appear linked to structure in these forests (de Oliveira and Moraes 2013, de Oliveira et al 2016, 2019).…”
Section: Section 1: Reframing Tropical Forest Savannization As Transimentioning
confidence: 99%
“…In the last decades, the anthropic activities in the Cerrado have been causing strong changes in this biome, in particular, in its conversion to pastures and the production of soybean and sugarcane (Klink and Moreira, 2002;Rodrigues et al, 2014), besides the high rates of deforestation that are causing a mosaic of natural forests and arable land (Biudes et al, 2015). That mosaic implies land cover changes, provoking changes in the distribution of solar energy that is available to the environment (Novais et al, 2015;Faria et al, 2018), which affects directly the biophysical process linked to regional energy balance (Rodrigues et al, 2016).…”
Section: Introductionmentioning
confidence: 99%